Shepherding Public Discourse Practices: Homiletic Form Aligned to the Logic Operative in Racial Rhetoric and Public Theological Discourse for Secular Liberal Democracies - Jackson, Maury (Cultural and religious studies, 2016)
Given that preaching is the primary mode of public theological discourse for most Christian ministers, an intellectual virtue of verbal restraint is required when practicing public theology and it is wise to address the ways that homilies can shepherd public discourse practices. A theology of rhetoric includes the homilist’s moral purpose. Homilies either enhance public discourse or pervert it. This essay sketches a pattern of sermon movement that respects the logic operative in public theology, given the social context of America. Homilies can help cultivate the pastoral care of public rhetoric by modeling discourse that nurtures the politics of accountability. While many call for a public ethos where divergent moral voices engage each other in highly contested arenas, a precondition to practicing effective public theology requires that one exercises discourse in a way that respects the social limits on the free exercise of religion. It is important that a public theology of rhetoric clarifies the original social agreement for acceptable religious discourse in the public arena. Homiletics, as a dimension of practical theology, can teach preachers methods of pastoral care for public discourse. The social agreement in liberal democracies to contain the combative nature of religious discourse assumes a logic that is circumscribed by commitments to (1) religious pluralism, (2) theological agnosticism, and (3) epistemological pragmatism. Here we propose that a sermon’s form, which implicitly touches upon these commitments, can tap into the basic modes of persuasion in secular liberal societies. This respects the moral purposes previously agreed upon and expected of partisans during highly contestable times. This calls for incarnational humility on the part of the Christian public theologian and it guides her/his practice.